Application of The PPP Scheme on The Tourism-Transportation, Case Study : The Concept Of Palopo City Tourism - Zulham Hafid; Windra Priatna Humang; Rakhmawati Natsir; Amiruddin Akbar Fisu (Faculty of Engineering, Andi Djemma University, 2022)
The stipulation of the Palopo City Regional Tourism Development Master Plan 2021 – 2025 makes the Palopo City tourism sector quite optimistic after the beginning of the pandemic. Until 2030, Palopo City targets 250,000 domestic tourists and 1800 foreign tourists. The tourism potential of Palopo City, especially in urban areas is quite promising with the construction of a culinary center and souvenirs, public space activities, and the development of culinary businesses. These potentials must be supported by adequate facilities and infrastructure, including accessibility. Meanwhile, public transportation in Palopo City is considered inadequate and not integrated with each other. The concept of Palopo City Tourism offers the integration of tourism activities in the urban areas of the city of Palopo by providing integrated tourism transportation modes, equipped with supporting infrastructure such as bus stops. However, the implementation of the concept will be constrained by funding problems given the limited regional finances and the demand to prioritize sectors that are more strategic than tourism. This paper will see how the implementation of the PPP scheme in the tourism sector, especially in the transportation aspect, namely in the concept of Palopo City Tourism, both in development, operation and potential benefits. From the results of the analysis of movement patterns and the location of tourist objects, 3 optimal routes were chosen that could accommodate the movement of tourists, namely the southern route, western route and northern route. From the results of the analysis of infrastructure needs, it is necessary to develop infrastructure in the form of shelters and pedestrian paths and their accessories at tourist attraction points and several commercial areas. In addition, several PPP financing schemes are also proposed which are considered suitable for the City Tour Palopo concept, including Concessions and Affermage/Lease schemes, such as Service Contracts and Management Contracts, Design-Build-Finance-Operate/Maintain (DBFO, DBFM or DBFO). /M), Build-Own-Lease-Transfer (BOLT).